2021
DOI: 10.1073/pnas.2016778118
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian cell proliferation requires noncatalytic functions of O-GlcNAc transferase

Abstract: O-GlcNAc transferase (OGT), found in the nucleus and cytoplasm of all mammalian cell types, is essential for cell proliferation. Why OGT is required for cell growth is not known. OGT performs two enzymatic reactions in the same active site. In one, it glycosylates thousands of different proteins, and in the other, it proteolytically cleaves another essential protein involved in gene expression. Deconvoluting OGT’s myriad cellular roles has been challenging because genetic deletion is lethal; complementation me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 93 publications
1
56
0
Order By: Relevance
“…These data could serve to increase glycosylation on desired substrates and influence glycosite selection while minimizing perturbations to the cell for O-GlcNAc engineering, in addition to the biological implications arising from differential substrate and site selection of the OGT TPR isoforms. The relationship between the TPR isoforms of OGT and biological function is a growing area of investigation as interactions and substrate selection through the TPR domain may be of particular relevance to normal O-GlcNAc regulation [6,10,31,48]. Comparison of glycoproteins in the presence of RFP(13) to a recently determined TPR interactome of ncOGT via a proximity-labeling approach [24] shows enrichment for similar biological processes, indicating that the TPR interactome and the enriched O-GlcNAcylated proteome correspond.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data could serve to increase glycosylation on desired substrates and influence glycosite selection while minimizing perturbations to the cell for O-GlcNAc engineering, in addition to the biological implications arising from differential substrate and site selection of the OGT TPR isoforms. The relationship between the TPR isoforms of OGT and biological function is a growing area of investigation as interactions and substrate selection through the TPR domain may be of particular relevance to normal O-GlcNAc regulation [6,10,31,48]. Comparison of glycoproteins in the presence of RFP(13) to a recently determined TPR interactome of ncOGT via a proximity-labeling approach [24] shows enrichment for similar biological processes, indicating that the TPR interactome and the enriched O-GlcNAcylated proteome correspond.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the essential requirement of OGT for substrate O-GlcNAcylation [10], deciphering the basis of OGT's substrate selection mechanisms has attracted much interest [2,11,12]. The canonical nucleocytoplasmic form of OGT (ncOGT) is composed of two domains: an N-terminal tetratricopeptide repeat (TPR) domain and a C-terminal catalytic domain (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some reports that stimulation of O -GlcNAc transferase, which catalyzes O -linked glycosylation of serine and threonine residues with UDP-N-Acetyl-GlcN, by GlcN promotes proliferation of murine ESC [ 30 , 31 , 32 ]. There was also a recent report that proliferation of mouse embryo fibroblasts (MEFs) requires noncatalytic functions of O -GlcNAc transferase [ 33 ]. However, the ESC and MEF lines used in those studies were isolated under conventional high glucose conditions and would not express GLUT2, and the ESC were treated with GlcN at concentrations that would be transported by GLUT1 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, that alone is unlikely to provide an understanding of crosstalk; we need to establish more clearly how OGT selects protein substrates, and we also need to account for a second enzymatic activity ascribed to OGT, its proteolytic function. A recent study has indicated that in some cell types, OGT can sustain cell proliferation through a non-catalytic function that needs to be fully characterised (109). This in turn also needs to be put into a spatial context, since OGT can function as different isoforms in distinct organelles within the cell, mitochondria, and nuclei being principal examples.…”
Section: Oglcnacylation: a Rheostat Connecting Metabolic Dysregulation To Transcriptionmentioning
confidence: 99%